2017
DOI: 10.1016/j.ebcr.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Epilepsy surgical outcome for epileptic and non epileptic seizures with posttraumatic stress disorder and depression

Abstract: A 48-year-old male was diagnosed with both drug resistant epilepsy and psychogenic nonepileptic seizures. Both diagnoses were confirmed by video-EEG monitoring. His epileptic seizures were a consequence of right mesial temporal sclerosis. He was diagnosed by a psychiatrist to have depression and posttraumatic stress disorder (PTSD). Following a right anterior temporal resection he became seizure free (both epileptic and nonepileptic) with a remarkable improvement in his psychiatric comorbidities leading to sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Sometimes patients with multiple seizure semiologies were perceived as less likely to be candidates for focal surgical interventions. Additionally, patients with comorbid epilepsy and dissociative seizures may be inaccurately viewed as poor surgical candidates [55,56]. Because a patient generally is presumed to have epilepsy prior to VEM, providers may delay referral for patients that were perceived as less ideal surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes patients with multiple seizure semiologies were perceived as less likely to be candidates for focal surgical interventions. Additionally, patients with comorbid epilepsy and dissociative seizures may be inaccurately viewed as poor surgical candidates [55,56]. Because a patient generally is presumed to have epilepsy prior to VEM, providers may delay referral for patients that were perceived as less ideal surgical candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with epilepsy suffer from high rates of traumas and falls, although only one study has identified a higher risk of injury [24]. The higher rate of epilepsy is well-known; patients with epilepsy may also suffer from PNES Bold values statistically significant at P b 0.01. and vice versa [25,26]. Patients with PNES are more likely not only to suffer from personal problems but also to have a lower quality of life [5,27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a few retrospective uncontrolled single-case reports might suggest that while right amygdalohippocampectomy could ameliorate PTSD, left amygdalohippocampotomy does not protect against developing PTSD. [3][4][5] The authors 1 rightly question whether the combination of hippocampotomy and amygdalotomy may account for some of the benefits we report. Indeed, the observations in our original report do not strictly parse potential roles of amygdala and hippocampus in maintaining PTSD.…”
mentioning
confidence: 89%